Relationship between the degree of creativity and the quality of design outcomes (2017)
This work analyses the relationship between the degree of creativity, measured through the level of novelty and the level of usefulness, and the quality of the design outcomes. To do so, a total of twelve conceptual designs obtained in a design experiment were measured and compared. In this experiment, four teams of three designers solved different design problems, applying brainstorming, SCAMPER and functional analysis as design methods. The quality of the design solutions have been evaluated in terms of feasibility and effectiveness by experts through a questionnaire. Feasibility and effectiveness were then compared with the novelty, usefulness and creativity, the results showing that as novelty increases, feasibility tends to be lower, and the more usefulness the design offers, the more effective it is.